Synthesis and Characterization of 3-(Pyridin-2-ylmethyl)pentane-2,4-dione - Zhang, Xiang; Lei, Lu; You, Qingliang; Zhang, Aiqing; Xie, Guangyong (Asian Journal of Chemistry, 2012)
A new compound, 3-(pyridin-2-ylmethyl)-pentane-2,4-dione was synthesized successfully and characterized by 1H NMR, IR, MS and elemental analysis.